2019
DOI: 10.33369/insight.14.1.63-72
|View full text |Cite
|
Sign up to set email alerts
|

Penilaian Value at Risk Dengan Pendekatan Extreme Value Theorydan Generalized Pareto Distribution Studi Kasus Bank Bumn Di Indonesia Pada Periode Tahun 2008-2018

Abstract: Perkembangan sektor perbankan di Indonesia dalam 10 tahun mengalami pertumbuhan yang agresif, tetapi juga memperhatikan rasio modal berdasarkan risiko sesuai dengan ketentuan otoritas. Bank BUMN di Indonesia menguasasi ?45% dari total aset pada sektor perbankan, dan memiliki rasio penyediaan modal minimum yang lebih tinggi dari yang disyaratkan otoritas. Penelitian in imembahas perhitungan VaR dengan metode GEV dan GPD, serta membandingkannya dengan rasio penyediaan modal minimum bank. Hasil perhitungan dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…VaR is an approach to measure the loss threshold value of a portfolio to control internal risk and as an investment policy consideration (Meng & Taylor, 2020). Research Akhmadi et al (2019) measures the level of risk by applying the VaR approach to estimate the maximum loss of a portfolio within a certain period and level of probability. Mathematically, the VaR equation with a certain horizon and confidence level is as follows Tsay (2010):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VaR is an approach to measure the loss threshold value of a portfolio to control internal risk and as an investment policy consideration (Meng & Taylor, 2020). Research Akhmadi et al (2019) measures the level of risk by applying the VaR approach to estimate the maximum loss of a portfolio within a certain period and level of probability. Mathematically, the VaR equation with a certain horizon and confidence level is as follows Tsay (2010):…”
Section: Methodsmentioning
confidence: 99%
“…Value at risk (VaR) is a tool for estimating the reduction in risk of return with a certain time horizon and confidence value. Akhmadi et al (2019) found that the GPD method outperformed EVT and was very close. with the capital adequacy ratio (CAR).…”
Section: Introductionmentioning
confidence: 92%